Pengaruh model pembelajaran inkuiri terbimbing terhadap keterampilan proses sains dan hasil belajar IPA siswa SD - Djufri, Elyas; Ardhian, Trio (Jurnal Madako Education, 2023)
The purpose of this study was to determine the effect of the guided inquiry learning model on science process skills and science learning outcomes using the posttest-only control group design. This study was conducted on fourth-grade students of Galang District State Elementary School. The study population was 125 students, and the sample was 64 students. Scientific attitude data were collected using a questionnaire method, and science learning outcomes data were collected using a test method. Data were analyzed using MANOVA, which was assisted by SPSS 20.00 for Windows. The results of the study showed: (1) there were differences in science process skills and science learning outcomes between students who learned using guided inquiry learning model and conventional learning model (p<0.05), (2) there were significant differences in science process skills in science learning between students who learned using guided inquiry learning model and conventional learning model (p<0.05), (3) there were significant differences in science learning outcomes between students who learned using guided inquiry learning model and conventional learning model (p<0.05).